AN EVALUATION ON ONLINE LEARNING BY DATA VISUALIZATION: A CASE STUDY FROM INFORMATION TECHNOLOGY EDUCATION PROGRAM - Fitri, Sulidar; Lubis, Maesaroh (Universitas Muhammadiyah Surakarta, 2024)
The result of learning process can be seen using scores from the exam as a result for evaluating the learning quality. This study focused on comparing the learning outcomes in Universitas Muhammadiyah Tasikmalaya (UMTAS) students especially one class in Information Technology Education Program between face-to-face learning and online learning. The learning process is observed in order to gain some insight about the difference number of academic performance and student’s perception between face-to-face online learning. The comparative results of this research will be described through data visualization using R programming language. Data visualization using R programming language will result in form of numbers summary data and graphics. The results of this study showed that the exam score and student’s perception after face-to-face learning is higher than online learning. This study shows around 93% students from Information Technology Education Department demanded more face-to-face in class than online learning.